CHARACTER ACCENTUATION IN ADOLESCENCE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
this article covers the character traits, types and classification experienced by adolescents.The article provides important recommendations to parents.